Qualitative investigation of the impact of internationalization of education on host community's eating habit. Issue 2 (21st November 2019) - Eluwole, Kayode Kolawole; Lasisi, Taiwo Temitope; Elidemir, Servet Nasifoglu; Guzel, Elif
Abstract : Although education tourism has over the years enjoyed great attention by scholars largely because of its impact in shaping both the economic and political landscape of nations, an ample number of such studies have focused on the impact of the host community on the adaptation and survival of the sojourning foreign students or education tourists. There has been significant research into student's acculturation, mobility, and the likes, but research on the reverse impact of sociocultural interaction of these education tourists on their host communities is scarce. North Cyprus, a small island state with economic dependence on education, is a thriving host community for a substantial number of an education tourist. This study explores the influence of internationalization of education on the food consumption habit of indigenes of their host community. Data generated from a focus group of North Cyprus indigenes were used to examine how the influx of educational tourists have altered and shaped their eating behavior and culture. Current study contributes to both literature and tourism sectors by showcasing the importance of cultural transfer of education tourism.